Sistem Pakar Berbasis Web untuk Diagnosa Penyakit pada Kucing Persia Medium: Sistem Pakar Berbasis Web untuk Diagnosa Penyakit pada Kucing Persia Medium - Zidane Chesa Wardana; Farida, Intan Nur; Dara, Made Ayu Dusea Widya (Universitas Nusantara PGRI Kediri, 2023)
This research creates a web-based expert system that uses the Bayes method for diagnosing disease in Persian Medium cats. This system offers a cheaper and more effective solution for cat owners to get an early diagnosis of disease without having to go to expensive veterinary clinics. The results of calculations using the Naive Bayes method show that the largest posterior value P(P2|G2|G7|G11) is 0.0093, which is then normalized to 100%, indicating that the cat in this case may have hair ball disease. Thus, it can be concluded that the cat in this case has hair ball disease. Persian Medium cat owners can use this expert system to diagnose their cat's disease more cheaply and effectively.